Electrical characterisation of simple a-Si:H and nc-Si devices on paper substrates deposited by hot wire chemical vapour deposition and printing techniques - Nemalili, Fhatuwani Patrick (Department of Physics, 2014)
Includes bibliographical references (leaves 68-72).